2019
DOI: 10.1021/acscatal.8b04190
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Monoxide Oxidation Promoted by a Highly Active Strained PdO Layer at the Surface of Au30Pd70(110)

Abstract: The evolution of the Au 30 Pd 70 (110) surface was studied by coupling grazing incidence X-ray diffraction and mass spectrometry under oxygen-rich conditions at moderate temperatures (300 to 470 K). This allows us to correlate the depth profile of its structure to its catalytic properties for carbon monoxide (CO) oxidation. Under increasing pressure from ultrahigh vacuum up to 100 mbar, both oxygen and CO induce Pd segregation, even at room temperature. However, in pure oxygen the surface is reorganized with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 68 publications
(179 reference statements)
0
5
0
Order By: Relevance
“…The Pd70Au30(110) (from SPL) is an unreconstructed Au-rich (~ 85-90%) surface under stable conditions after preparation cycles (ion bombardment followed by annealing). We have shown that upon exposure to CO, Pd segregates to the surface and the surface becomes rough (corrugation ~0.05 nm) [4]. In presence of oxygen, the surface reconstructs exhibiting a (nx2) structure ((1x2) with vacancies) and, as for CO, Pd segregates to the surface (Fig.…”
mentioning
confidence: 79%
See 2 more Smart Citations
“…The Pd70Au30(110) (from SPL) is an unreconstructed Au-rich (~ 85-90%) surface under stable conditions after preparation cycles (ion bombardment followed by annealing). We have shown that upon exposure to CO, Pd segregates to the surface and the surface becomes rough (corrugation ~0.05 nm) [4]. In presence of oxygen, the surface reconstructs exhibiting a (nx2) structure ((1x2) with vacancies) and, as for CO, Pd segregates to the surface (Fig.…”
mentioning
confidence: 79%
“…In the case of P(O2)/P(CO)>>10, SXRD shows that an oxide strained layer (< 10 atomic layers) is formed (Fig. 3) that is the active surface in such conditions [4]. Surface oxidation and its role in the CO oxidation strongly depend on the reaction conditions and for a same system surface oxidation can be either noxious or the best option to the reaction.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is a different reaction mechanism undergoes in CO oxidation during oxygen-rich conditions. Saint-Lager et al 149 reported that the surface segregation of CO-induced Pd clusters is dominant in the case of low O 2 /CO ratio; however, in the case of high O 2 /CO ratio, O 2 penetrated into the lattice to form the segregated PdO thin layer on the surface of AuPd alloys. Compared with the usual PdO phase, the AuPd@PdO thin layer showed similar lattice constants to the high-pressure tetragonal phase, which contracted in volume and thus led to the compressive strain.…”
Section: Insight Into the Active Sites'mentioning
confidence: 99%
“…There are also many explorations on the reasons for the activity improvement of bimetallic catalysts. Saint-Lager et al [26] studied the changes of AuPd particles during the reaction process. The evolution of the Au30Pd70(110) surface was examined by means of coupling grazing incidence X-ray diffraction and mass spectrometry under the oxygen-rich conditions at moderate temperatures (27 to 197 o C), so that the depth profile of the structure could correlate to its catalytic properties for carbon monoxide oxidation (Figure 6).…”
Section: Supported Noble Bimetal Catalystsmentioning
confidence: 99%